2020
DOI: 10.48550/arxiv.2012.00153
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anomalies in Radioactive Decay Rates: A Bibliography of Measurements and Theory

Abstract: Knowledge of the decay rates (or half-lives) of radioisotopes is critical in many fields, including medicine, archeology, and nuclear physics, to name just a few. Central to the many uses of radioisotopes is the belief that decay rates are fundamental constants of nature, just as the masses of the radioisotopes themselves are. Recently, the belief that decay rates are fundamental constants has been called into question following the observation of various reported anomalies in decay rates, such as apparent per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 195 publications
0
1
0
Order By: Relevance
“…is not the task of this study. But we would like to point out two works that were not included in the reviews [1,2], issues which are close to those we investigated, and in which the problem of connection of periodicities, existing in the decay signals, with cosmic factors are considered in one way or another. In [8], long-term measurements of the natural gammabackground were carried out and a search was made for correlations of the received signals with some geophysical factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…is not the task of this study. But we would like to point out two works that were not included in the reviews [1,2], issues which are close to those we investigated, and in which the problem of connection of periodicities, existing in the decay signals, with cosmic factors are considered in one way or another. In [8], long-term measurements of the natural gammabackground were carried out and a search was made for correlations of the received signals with some geophysical factors.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been an active discussion about observations of the variability of radioactive decay half-life in time. The positions of opponents today are expressed in [1], and supportersin [2]. The paper provides additional data about observations of such effects.…”
Section: Introductionmentioning
confidence: 94%
“…One of the most persistent misunderstandings concerning radionuclide metrology is the assertion that cyclic variations in measured decay rates are caused by space weather phenomena, in particular by neutrinos emitted from the Sun or dark matter [4]. Some authors are adamant in their claims that observed violations of the exponentialdecay law cannot be attributed to environmental conditions in the laboratory [5,6]. However, using historical weather data available on meteorological websites, a link with terrestrial weather could be established for several infamous experiments [1,2,4,[7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%